Curing agent, preparation method thereof and anticorrosive paint
By using a curing agent containing naphthalene dispersant in the anticorrosion coating, the problem of insufficient dispersion of graphene is solved, and the anticorrosion performance and service life of the anticorrosion coating are improved.
Patent Information
- Application Number
- CN202310942695.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
The dispersion of graphene in existing anticorrosion coatings is insufficient, and agglomeration is prone to occur, which affects the anticorrosion effect. The dispersion effect of existing dispersants on graphene is limited, especially at high temperatures or long-term storage.
A curing agent is adopted, including epoxy curing agent, graphene, naphthalene dispersant and solvent, in which the ammonium dinonyl naphthalene sulfonate in the naphthalene dispersant can bind to the π-π electrons of graphene to prevent graphene from being The sheet contacts to improve its dispersion.
Effectively prevent graphene from agglomerating during long storage or at high temperatures, improve the anticorrosion performance of anticorrosion coatings, enhance the physical barrier properties and permeability of the coating, and extend the service life.
Smart Images

Figure CN119431740A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of anti-corrosion coatings, and in particular to a curing agent and a preparation method and application thereof. Background Art
[0002] Graphene is widely used in the field of coatings because it can improve the anti-corrosion performance of coatings. At present, anti-corrosion coatings generally include an epoxy component (component A) and a curing agent component (component B) containing graphene, which are separately prepared before use. When needed, the curing agent component is added to the epoxy component to obtain an anti-corrosion coating, which is sprayed onto the surface of the device to be anti-corroded to achieve the anti-corrosion effect.
[0003] However, due to the poor wettability of graphene, it is easy to agglomerate, which will affect the stability of the curing agent component and thus the anti-corrosion effect of the anti-corrosion coating. Usually, a dispersant is added to the curing agent component to promote the dispersion and dissolution of graphene, but the addition of the dispersant will increase the components of the anti-corrosion coating, thereby poisoning the overall anti-corrosion performance of the coating, and the existing dispersant has limited effect on dispersing graphene, especially at 70 degrees Celsius or when stored for a long time, graphene is still prone to agglomeration.
[0004] Therefore, the dispersibility of graphene in the curing agent component needs to be further improved. Summary of the invention
[0005] In view of this, the present application provides a curing agent and a preparation method thereof, and an anti-corrosion coating, aiming to improve the dispersibility of graphene in the curing agent component.
[0006] The present application is implemented as follows: a curing agent includes: an epoxy curing agent, graphene, a naphthalene dispersant and a solvent, wherein the naphthalene dispersant includes dinonylnaphthalene ammonium sulfonate.
[0007] Optionally, in some embodiments of the present application, the mass ratio of the epoxy curing agent, the graphene, the naphthalene dispersant and the solvent is (30.43-58.58): (8.12-11.36): (3.02-3.67): (20.49-35.29).
[0008] Optionally, in some embodiments of the present application, the epoxy curing agent includes one or more of trimellitic acid, boron trifluoride, dicyandiamide, adipic acid dihydrazide, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, and phthalic anhydride; and / or
[0009] The graphene includes one or more of doped graphene and undoped graphene, and the doped graphene includes zinc oxide / graphene; and / or
[0010] The naphthalene dispersant further comprises one or more of polynaphthalene formaldehyde sulfonate sodium salt and ammonium naphthalene sulfonate formaldehyde condensate; and / or
[0011] The solvent includes one or more of n-butanol, xylene, toluene, N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, pyridine, tetrahydrofuran, ethylene glycol, acetone, methanol, ethanol, 1-propanol, dichloromethane, o-xylene, and n-hexane.
[0012] Optionally, in some embodiments of the present application, the curing agent further comprises a wetting agent; and / or
[0013] The curing agent also includes an anti-settling agent.
[0014] Optionally, in some embodiments of the present application, the wetting agent includes one or more of alkyl alcohol polyoxyethylene ether, β-hydroxyalkyl amide, cycloalkyl amide; and / or
[0015] The mass ratio of the graphene to the wetting agent is (8.12-11.36): (1.5-2.5); and / or
[0016] The anti-settling agent includes one or more of polyethylene wax, bentonite, polyamide wax, and cellulose; and / or
[0017] The mass ratio of the graphene to the anti-settling agent is (8.12-11.36):(4.62-10.7).
[0018] Optionally, in some embodiments of the present application, the curing agent includes epoxy curing agent, zinc oxide / graphene, undoped graphene, naphthalene dispersant, n-butanol, xylene, wetting agent, polyethylene wax, and bentonite; the mass ratio of the epoxy curing agent, the zinc oxide / graphene, the undoped graphene, the naphthalene dispersant, the n-butanol, the xylene, the wetting agent, the polyethylene wax, and the bentonite is (30.43~58.58): (4.5~6.8): (3.62~4.56): (3.02~3.67): (9.09~16.04): (11.4~19.25): (1.5~2.5): (2.31~6.42): (2.31~4.28).
[0019] Accordingly, the present application also provides a method for preparing a curing agent, comprising:
[0020] Providing a graphene dispersion liquid, wherein the graphene dispersion liquid includes a first graphene and a first solvent;
[0021] Providing a zinc salt, and adding the zinc salt to the graphene dispersion to react to obtain a zinc oxide / graphene composite material;
[0022] A naphthalene dispersant is provided, wherein the naphthalene dispersant includes dinonylnaphthalene ammonium sulfonate, and the zinc oxide / graphene composite material is mixed with an epoxy curing agent, the naphthalene dispersant, and a second solvent to obtain a curing agent.
[0023] Optionally, in some embodiments of the present application, the first graphene includes graphene oxide; and / or
[0024] The first solvent includes one or more of N,N-dimethylformamide, n-butanol, xylene, toluene, dimethyl sulfoxide, N-methyl-2-pyrrolidone, pyridine, tetrahydrofuran, ethylene glycol, acetone, methanol, ethanol, 1-propanol, dichloromethane, o-xylene, and n-hexane; and / or
[0025] The zinc salt includes one or more of zinc nitrate, zinc chloride, zinc sulfate, zinc hypochlorite, and zinc tetrafluoroborate.
[0026] Optionally, in some embodiments of the present application, in the graphene dispersion, the mass concentration of the first graphene is 0.35 mg / mL to 0.65 mg / mL; and / or
[0027] The mass ratio of the first graphene to the zinc salt is (0.05-0.15):20; and / or
[0028] The temperature at which the zinc salt reacts with the graphene dispersion is 270° C. to 370° C.; and / or
[0029] The reaction time of the zinc salt and the graphene dispersion is 25 min to 35 min.
[0030] Optionally, in some embodiments of the present application, the method for preparing the curing agent further includes providing a wetting agent, an anti-settling agent and a second graphene, and mixing the wetting agent, the anti-settling agent and the second graphene with the zinc oxide / graphene composite material, the epoxy curing agent, the naphthalene dispersant and the first solvent to obtain the curing agent.
[0031] Correspondingly, the present application also provides an anti-corrosion coating, comprising epoxy resin and the above-mentioned curing agent.
[0032] Optionally, in some embodiments of the present application, the epoxy resin includes one or more of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, aliphatic epoxy resin, and alicyclic epoxy resin; and / or
[0033] The mass ratio of the epoxy resin to the curing agent is 1:(0.9-1).
[0034] The curing agent provided in the present application, i.e., component B in the anti-corrosion coating, includes an epoxy curing agent, graphene, a naphthalene dispersant and a solvent. The benzene ring structure in the naphthalene dispersant can combine with the π-π electrons in the graphene to hinder the contact between the graphene sheets, effectively preventing the graphene from agglomerating due to long-term storage of the curing agent or high temperature, and the dinonylnaphthalene ammonium sulfonate in the naphthalene dispersant can also react with the epoxy resin of the anti-corrosion coating to promote the curing of the epoxy resin; and the graphene sheet structure is stacked and staggered, and a "maze-like" shielding structure can be formed in the anti-corrosion coating to form a shielding barrier, which effectively inhibits the infiltration, penetration and diffusion of the corrosive medium, and improves the physical barrier properties of the coating prepared by the anti-corrosion coating. At the same time, graphene can also extend the penetration and diffusion path of the corrosive medium, thereby providing the coating with anti-permeability and service life; the epoxy curing agent can chemically react with the epoxy resin (component A) of the anti-corrosion coating to form a network of three-dimensional polymers of the epoxy resin, thereby improving the adhesion of the anti-corrosion coating, as well as the wear resistance and hardness of the coating after being made. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0036] Figure 1 It is a flow chart of a method for preparing a curing agent provided in an embodiment of the present application. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0038] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0039] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0040] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0041] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0042] The technical solution of this application is as follows:
[0043] In a first aspect, an embodiment of the present application provides a curing agent, including: an epoxy curing agent, graphene, a naphthalene dispersant and a solvent, wherein the naphthalene dispersant includes dinonylnaphthalene ammonium sulfonate.
[0044] The curing agent provided in the present application, i.e., component B in the anti-corrosion coating, includes an epoxy curing agent, graphene, a naphthalene dispersant and a solvent. The benzene ring structure in the naphthalene dispersant can combine with the π-π electrons in the graphene to hinder the contact between the graphene sheets, effectively preventing the graphene from agglomerating due to long-term storage of the curing agent or high temperature, and the dinonylnaphthalene ammonium sulfonate in the naphthalene dispersant can also react with the epoxy resin of the anti-corrosion coating to promote the curing of the epoxy resin; and the graphene sheet structure is stacked and staggered, and a "maze-like" shielding structure can be formed in the anti-corrosion coating to form a shielding barrier, which effectively inhibits the infiltration, penetration and diffusion of the corrosive medium, and improves the physical barrier properties of the coating prepared by the anti-corrosion coating. At the same time, graphene can also extend the penetration and diffusion path of the corrosive medium, thereby providing the coating with anti-permeability and service life; the epoxy curing agent can chemically react with the epoxy resin (component A) of the anti-corrosion coating to form a network of three-dimensional polymers of the epoxy resin, thereby improving the adhesion of the anti-corrosion coating, as well as the wear resistance and hardness of the coating after being made.
[0045] In some embodiments, the mass ratio of the epoxy curing agent, the graphene, the naphthalene dispersant and the solvent is (30.43-58.58): (8.12-11.36): (3.02-3.67): (20.49-35.29), for example, it can be (40-50): (8.12-11.36): (3.02-3.67): (20.49-35.29), ( 30.43-58.58): (9-10): (3.02-3.67): (20.49-35.29), (30.43-58.58): (8.12-11.36): (3.2-3.5): (20.49-35.29), (30.43-58.58): (8.12-11.36): (3.02-3.67): (25-30), etc. Within the mass ratio range, the dispersant is beneficial to the dispersion of the graphene.
[0046] In some embodiments, the epoxy curing agent includes one or more of trimellitic acid, boron trifluoride, dicyandiamide, adipic acid dihydrazide, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, and phthalic anhydride.
[0047] In some embodiments, the graphene includes one or more of doped graphene and undoped graphene. The doped graphene includes zinc oxide / graphene, silicon nitride / graphene, aluminum oxide / graphene, titanium dioxide / graphene. Further, the graphene is nanographene.
[0048] In at least one embodiment, the graphene includes the doped graphene and the undoped graphene. The benzene ring structure in the naphthalene dispersant can combine with the π-π electrons in the graphene, inserting the doped graphene between the undoped graphene sheets, hindering the contact of the graphene sheets, and effectively preventing the graphene from agglomerating due to long time or high temperature.
[0049] Furthermore, the mass ratio of the doped graphene to the undoped graphene is (4.5-6.8): (3.62-4.56), for example, (5-6.5): (3.62-4.56), (5.5-6): (3.62-4.56), (4.5-6.8): (3.8-4), etc. Within the mass ratio range, it is beneficial to suppress the agglomeration of graphene.
[0050] In some embodiments, the naphthalene dispersant further comprises one or more of polynaphthalene formaldehyde sulfonate sodium salt and ammonium naphthalene sulfonate formaldehyde condensate.
[0051] In at least one embodiment, the naphthalene dispersant includes dinonyl naphthalene ammonium sulfonate and the ammonium naphthalene sulfonate formaldehyde condensate. The mass ratio of the dinonyl naphthalene ammonium sulfonate and the ammonium naphthalene sulfonate formaldehyde condensate is 3:1. Within the mass ratio range, it is beneficial to combine with the graphene to avoid graphene agglomeration.
[0052] In some embodiments, the solvent includes one or more of n-butanol, xylene, toluene, N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, pyridine, tetrahydrofuran, ethylene glycol, acetone, methanol, ethanol, 1-propanol, dichloromethane, o-xylene, and n-hexane.
[0053] In at least one embodiment, the solvent includes the n-butanol and the xylene. The mass ratio of the n-butanol to the xylene is (9.09-16.04): (11.4-19.25), for example, (10-15): (3.62-4.56), (12-14): (3.62-4.56), (4.5-6.8): (12-18), etc. Within the mass ratio range, the curing agent is conducive to stability.
[0054] In some embodiments, the curing agent further includes a wetting agent.
[0055] Furthermore, the wetting agent includes one or more of alkyl alcohol polyoxyethylene ether, β-hydroxyalkyl amide, and cycloalkyl amide.
[0056] In some embodiments, the carbon number of the alkyl group in the alkyl alcohol polyoxyethylene ether is 8-16.
[0057] In some embodiments, the mass ratio of the graphene to the wetting agent is (8.12-11.36): (1.5-2.5), for example, (8.5-10.5): (1.5-2.5), (9-10): (1.5-2.5), (8.12-11.36): (1.6-2.2), (8.12-11.36): (1.8-2), etc. Within the mass ratio range, the wetting effect of the wetting agent on the graphene is beneficial, thereby promoting the combination of the naphthalene dispersant and the graphene and improving the dispersibility of the graphene.
[0058] In some embodiments, the curing agent further includes an anti-settling agent.
[0059] Furthermore, the anti-settling agent includes one or more of polyethylene wax, bentonite, polyamide wax, and cellulose.
[0060] In some embodiments, the mass ratio of the graphene to the anti-settling agent is (8.12-11.36): (4.62-10.7), for example, (8.5-10.5): (4.62-10.7), (9-10): (4.62-10.7), (8.12-11.36): (5-8), (8.12-11.36): (6-7), etc. Within the mass ratio range, the anti-settling agent can improve the flowability and wettability of the curing agent, and also contribute to the stability of the curing agent during storage.
[0061] In at least one embodiment, the anti-settling agent includes the polyethylene wax and the bentonite. The mass ratio of the polyethylene wax to the bentonite is (2.31-6.42): (2.31-4.28), for example, it can be (3-6): (2.31-4.28), (4-5): (2.31-4.28), (2.31-6.42): (2.5-4), (2.31-6.42): (3-3.5), etc.
[0062] Second, see Figure 1 The present application also provides a method for preparing a curing agent, comprising:
[0063] S11, providing a graphene dispersion liquid, wherein the graphene dispersion liquid includes a first graphene and a first solvent;
[0064] S12, providing a zinc salt, and adding the zinc salt to the graphene dispersion to react to obtain a zinc oxide / graphene composite material;
[0065] S13, providing a naphthalene dispersant, wherein the naphthalene dispersant includes dinonylnaphthalene ammonium sulfonate, and mixing the zinc oxide / graphene composite material with an epoxy curing agent, the naphthalene dispersant, and a second solvent to obtain a curing agent.
[0066] It should be noted that the zinc oxide / graphene composite material is a composite material of zinc oxide doped with graphene.
[0067] In S11:
[0068] In some embodiments, the first solvent includes one or more of N,N-dimethylformamide, n-butanol, xylene, toluene, dimethyl sulfoxide, N-methyl-2-pyrrolidone, pyridine, tetrahydrofuran, ethylene glycol, acetone, methanol, ethanol, 1-propanol, dichloromethane, o-xylene, and n-hexane.
[0069] In some embodiments, in the graphene dispersion, the mass concentration of the first graphene is 0.35 mg / mL to 0.65 mg / mL, for example, 0.36 mg / mL to 0.62 mg / mL, 0.38 mg / mL to 0.6 mg / mL, 0.4 mg / mL to 0.58 mg / mL, 0.45 mg / mL to 0.55 mg / mL, 0.48 mg / mL to 0.5 mg / mL, etc. Within the mass concentration range, the dispersion and dissolution of the first graphene is facilitated.
[0070] In some embodiments, the method for preparing the graphene dispersion includes: providing a first graphene and a first solvent, mixing and ultrasonically treating the first graphene to obtain a graphene dispersion. It is understood that the ultrasonic treatment can promote the first graphene to be uniformly dispersed and dissolved in the first solvent. Further, the ultrasonic treatment time can be 1.5h to 2.5h, for example, 1.6h to 2.4h, 1.7h to 2.3h, 1.8h to 2.2h, 1.9h to 2h, etc.
[0071] In some embodiments, the first graphene includes graphene oxide.
[0072] In S12:
[0073] In some embodiments, the zinc salt includes one or more of zinc nitrate, zinc chloride, zinc sulfate, zinc hypochlorite, and zinc tetrafluoroborate.
[0074] In some embodiments, the mass ratio of the first graphene to the zinc salt is (0.05-0.15):20, for example, (0.06-0.14):20, (0.07-0.13):20, (0.08-0.12):20, (0.09-0.1):20, etc. Within the mass ratio range, the first graphene and the zinc salt are conducive to reacting.
[0075] In some embodiments, after adding the zinc salt to the graphene dispersion, stirring is further included. Further, the stirring time is 35min to 55min, for example, 38min to 52min, 40min to 50min, 41min to 48min, 42min to 46min, 44min to 45min, etc. It can be understood that the stirring is conducive to the full contact between the zinc salt and the graphene dispersion.
[0076] In some embodiments, the temperature for the reaction of the zinc salt with the graphene dispersion is 270°C to 320°C, for example, 270°C to 320°C, 270°C to 320°C, 270°C to 320°C, 270°C to 320°C, 270°C to 320°C, 270°C to 320°C, etc. The time for the reaction of the zinc salt with the graphene dispersion is 25min to 35min, for example, 26min to 34min, 27min to 33min, 28min to 32min, 29min to 30min, etc. In this way, it is beneficial for the zinc salt to react efficiently with the graphene dispersion to obtain a zinc oxide / graphene composite material.
[0077] Furthermore, the reaction of the zinc salt with the graphene dispersion comprises: adding the zinc salt to the graphene dispersion, placing the mixture at room temperature, heating the mixture to a reaction temperature, and reacting the mixture to obtain a zinc oxide / graphene composite material.
[0078] In some embodiments, the heating rate is 8°C / min to 12°C / min, for example, 8.5°C / min to 11.5°C / min, 9°C / min to 11°C / min, 9.5°C / min to 10.5°C / min, etc.
[0079] In some embodiments, after the zinc salt reacts with the graphene dispersion, the step further includes cleaning the reaction product.
[0080] In some embodiments, the cleaning includes deionized water cleaning and alcohol cleaning.
[0081] In some embodiments, after cleaning the reaction product, the step further includes drying the cleaned product.
[0082] In some embodiments, the drying comprises vacuum drying, natural drying or heat drying.
[0083] In some embodiments, the drying temperature is 75°C to 85°C, for example, 76°C to 84°C, 77°C to 83°C, 78°C to 82°C, 79°C to 80°C, etc. The drying time is 1.5h to 2.5h, for example, 1.6h to 2.4h, 1.7h to 2.3h, 1.8h to 2.2h, 1.9h to 2h, etc. In this way, it is beneficial to remove the deionized water and alcohol introduced in the cleaning process to obtain the zinc oxide / graphene composite material.
[0084] In S13:
[0085] In some embodiments, the zinc oxide / graphene composite material is mixed with an epoxy curing agent, a naphthalene dispersant, and a second solvent, comprising:
[0086] S131: mixing the naphthalene dispersant and the second solvent to obtain a naphthalene dispersant solution;
[0087] S132: Mixing the naphthalene dispersant solution with the zinc oxide / graphene composite material and the epoxy curing agent to obtain a curing agent.
[0088] In some embodiments, in the dispersant solution, the mass fraction of the naphthalene dispersant is 12% to 18%, for example, 12.5% to 17.5%, 13% to 17%, 13.5% to 16%, 14% to 15%, etc. Within the mass fraction range, the naphthalene dispersant is conducive to dispersion and dissolution.
[0089] In some embodiments, the second solvent includes one or more of n-butanol, xylene, toluene, N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, pyridine, tetrahydrofuran, ethylene glycol, acetone, methanol, ethanol, 1-propanol, dichloromethane, o-xylene, and n-hexane.
[0090] In some embodiments, the method for preparing the curing agent further includes providing a wetting agent, and mixing the wetting agent with the zinc oxide / graphene composite material, the epoxy curing agent, the naphthalene dispersant, and the first solvent.
[0091] The preparation method of the wetting agent is similar to the preparation method of the naphthalene dispersant, which will not be described in detail here.
[0092] In some embodiments, the method for preparing the curing agent further includes providing an anti-settling agent, and mixing the anti-settling agent with the zinc oxide / graphene composite material, the epoxy curing agent, the naphthalene dispersant, and the first solvent.
[0093] In some embodiments, the method for preparing the curing agent further includes providing a second graphene, and mixing the second graphene with the zinc oxide / graphene composite material, the epoxy curing agent, the naphthalene dispersant, and the first solvent.
[0094] It can be understood that the second graphene includes non-doped graphene. During mixing, the second graphene can be first mixed with the zinc oxide / graphene composite material, and then the wetting agent is added. After the wetting agent wets the surface of the second graphene and the zinc oxide / graphene composite material, the naphthalene dispersant is added. The benzene ring structure in the naphthalene dispersant is combined with the zinc oxide / graphene composite material through π-π electrons, and the zinc oxide / graphene composite material is interspersed between the graphene sheets to inhibit the agglomeration and sedimentation of the graphene.
[0095] The epoxy curing agent, naphthalene dispersant, wetting agent and anti-settling agent are as described above and will not be described in detail here.
[0096] In a third aspect, an embodiment of the present application also provides an anti-corrosion coating comprising an epoxy resin and the above-mentioned curing agent.
[0097] In some embodiments, the epoxy resin includes one or more of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, aliphatic epoxy resin, and alicyclic epoxy resin.
[0098] In some embodiments, the mass ratio of the epoxy resin to the curing agent is 1:(0.9-1), for example, it can be 1:(0.91-0.99), 1:(0.92-0.98), 1:(0.93-0.97), 1:(0.94-0.96), etc.
[0099] It can be understood that when the curing agent and epoxy resin are mixed to prepare the anti-corrosion coating, some wetting agents and dispersants may participate in the curing reaction and eventually evaporate with the solvent, which will not affect the anti-corrosion effect of the anti-corrosion coating.
[0100] The anti-corrosion coating provided in the present application has good anti-corrosion effect, high adhesion, and the prepared coating has good wear resistance and high hardness.
[0101] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0102] Example 1
[0103] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0104] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0105] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0106] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3.3:2:4:3:3:5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0107] Example 2
[0108] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0109] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0110] Weigh dinonylnaphthalene sulfonate ammonium and polynaphthalene formaldehyde sulfonate sodium salt dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0111] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3.3:2:4:3:3:5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0112] Example 3
[0113] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0114] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0115] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0116] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3:2:4:3:3:5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0117] Example 4
[0118] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0119] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0120] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0121] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3.67:2:4:3:3:5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0122] Example 5
[0123] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0124] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0125] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0126] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3.3:2:4:3:3:4.5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0127] Example 6
[0128] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0129] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0130] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0131] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3.3:2:4:3:3:6.8, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0132] Example 7
[0133] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0134] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0135] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0136] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3.3:2:3.62:3:3:5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0137] Example 8
[0138] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0139] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0140] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0141] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3:2:4.56:3:3:5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0142] Example 9
[0143] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0144] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0145] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0146] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3.3:1.5:4:3:3:5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0147] Example 10
[0148] This embodiment provides a curing agent, and the preparation method thereof is as follows:
[0149] Weigh 100 mg of graphene oxide, mix it with 200 mL of N,N-dimethylformamide, and then put it into an ultrasonic cleaner for 2 hours. After the ultrasonic treatment, weigh 20 g of Zn(NO3)2, add it to the graphene oxide dispersion and stir it for 45 minutes. After the stirring is completed, transfer the mixed solution to a container, seal it and put it into a high-pressure reactor, heat it to 320°C at 10°C / min, react for 30 minutes, cool it to room temperature after the reaction is completed, and then centrifuge the product, use deionized water and alcohol twice respectively, and then dry it in an oven at 80°C for 2 hours to obtain a nano zinc oxide / graphene composite material;
[0150] Weigh dinonylnaphthalenesulfonate ammonium and naphthalenesulfonate formaldehyde condensate dispersants in a mass ratio of 3:1, and prepare the dispersants into a 15% dispersant solution with a mixed solution of n-butanol and xylene; weigh β-hydroxyalkylamide wetting agent and prepare a wetting agent solution;
[0151] Ethylenediamine, the above dispersant, β-hydroxyalkylamide, graphene, polyethylene wax, bentonite and a composite material of nano zinc oxide / graphene are mixed in a mass ratio of 40:3.3:2.5:4:3:3:5, and n-butanol solvent is added until the mass ratio of all solvents to ethylenediamine is 30:40 to obtain a fixing agent.
[0152] Comparative Example
[0153] This comparative example is substantially the same as Example 1, except that no dispersant is added in this comparative example.
[0154] Application Example 1
[0155] Application Example 1 provides an anti-corrosion paint and an anti-corrosion coating, and the preparation method includes:
[0156] The curing agent of Example 1 is mixed with epoxy resin to obtain an anti-corrosion coating;
[0157] A zinc substrate is provided, and the anti-corrosion paint is sprayed on the surface of the substrate to form an anti-corrosion coating.
[0158] Application Examples 2 to 10
[0159] Application Examples 2 to 10 are substantially the same as Application Example 1, except that the curing agent of Example 1 is replaced by the curing agent of Examples 2 to 10, respectively.
[0160] Application comparison
[0161] The application comparative example is substantially the same as the application example 1, except that the curing agent of the example 1 is replaced by the curing agent of the comparative example.
[0162] The impact strength tester was used to test the anti-corrosion coatings in application examples 1 to 10 and the application comparison example; the salt spray resistance of the anti-corrosion coating was measured in an artificially simulated salt spray environment, wherein the conditions of the artificially simulated salt spray environment were: 5% sodium chloride saline solution, pH value 6 to 7, sprayed as a spray, the test temperature was 35°C, and the sedimentation rate of the salt spray was 1 to 3 ml / 80 cm 2 The impact strength and salt spray resistance of the anti-corrosion coating are shown in Table 1.
[0163] Table 1
[0164]
[0165] As can be seen from Table 1, compared with the anti-corrosion coating of the comparative example, the impact strength of the anti-corrosion coating of Examples 1 to 10 is significantly improved, and the salt spray resistance time is also significantly extended, indicating that the curing agent improved in the present application is applied to the anti-corrosion coating, which can effectively improve the impact strength and salt spray resistance time of the anti-corrosion coating. Specifically, the impact strength of the anti-corrosion coating of Examples 1 to 10 is above 50kg·cm, indicating that it is tightly combined with the zinc substrate and is not easy to fall off; and the salt spray resistance time of the anti-corrosion coating of Examples 1 to 10 is above 1000h, indicating that it can play an excellent anti-corrosion effect for a long time and the performance is effectively improved.
[0166] The curing agent and its preparation method, and the anti-corrosion coating provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A curing agent, characterized in that include: Epoxy curing agent, graphene, naphthalene dispersant and solvent, wherein the naphthalene dispersant comprises dinonylnaphthalene ammonium sulfonate.
2. The curing agent according to claim 1, characterized in that The mass ratio of the epoxy curing agent, the graphene, the naphthalene dispersant and the solvent is (30.43-58.58): (8.12-11.36): (3.02-3.67): (20.49-35.29).
3. The curing agent according to claim 1, characterized in that The epoxy curing agent includes one or more of trimellitic acid, boron trifluoride, dicyandiamide, adipic acid dihydrazide, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, and phthalic anhydride; and / or The graphene includes one or more of doped graphene and undoped graphene, and the doped graphene includes zinc oxide / graphene; and / or The naphthalene dispersant further comprises one or more of polynaphthalene formaldehyde sulfonate sodium salt and ammonium naphthalene sulfonate formaldehyde condensate; and / or The solvent includes one or more of n-butanol, xylene, toluene, N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, pyridine, tetrahydrofuran, ethylene glycol, acetone, methanol, ethanol, 1-propanol, dichloromethane, o-xylene, and n-hexane.
4. The curing agent according to claim 1, characterized in that The curing agent further comprises a wetting agent; and / or The curing agent also includes an anti-settling agent.
5. The curing agent according to claim 4, characterized in that The wetting agent includes one or more of alkyl alcohol polyoxyethylene ether, β-hydroxyalkyl amide, and cycloalkyl amide; and / or The mass ratio of the graphene to the wetting agent is (8.12-11.36): (1.5-2.5); and / or The anti-settling agent includes one or more of polyethylene wax, bentonite, polyamide wax, and cellulose; and / or The mass ratio of the graphene to the anti-settling agent is (8.12-11.36):(4.62-10.7).
6. The curing agent according to any one of claims 1 to 5, characterized in that The curing agent includes epoxy curing agent, zinc oxide / graphene, non-doped graphene, naphthalene dispersant, n-butanol, xylene, wetting agent, polyethylene wax and bentonite; the mass ratio of the epoxy curing agent, the zinc oxide / graphene, the non-doped graphene, the naphthalene dispersant, the n-butanol, the xylene, the wetting agent, the polyethylene wax and the bentonite is (30.43-58.58): (4.5-6.8): (3.62-4.56): (3.02-3.67): (9.09-16.04): (11.4-19.25): (1.5-2.5): (2.31-6.42): (2.31-4.28).
7. A method for preparing a curing agent, characterized in that: include: Providing a graphene dispersion liquid, wherein the graphene dispersion liquid includes a first graphene and a first solvent; Providing a zinc salt, and adding the zinc salt to the graphene dispersion to react to obtain a zinc oxide / graphene composite material; A naphthalene dispersant is provided, wherein the naphthalene dispersant includes dinonylnaphthalene ammonium sulfonate, and the zinc oxide / graphene composite material is mixed with an epoxy curing agent, the naphthalene dispersant, and a second solvent to obtain a curing agent.
8. The preparation method according to claim 7, characterized in that: The first graphene comprises graphene oxide; and / or The first solvent includes one or more of N,N-dimethylformamide, n-butanol, xylene, toluene, dimethyl sulfoxide, N-methyl-2-pyrrolidone, pyridine, tetrahydrofuran, ethylene glycol, acetone, methanol, ethanol, 1-propanol, dichloromethane, o-xylene, and n-hexane; and / or The zinc salt includes one or more of zinc nitrate, zinc chloride, zinc sulfate, zinc hypochlorite, and zinc tetrafluoroborate.
9. The preparation method according to claim 7, characterized in that: In the graphene dispersion, the mass concentration of the first graphene is 0.35 mg / mL to 0.65 mg / mL; and / or The mass ratio of the first graphene to the zinc salt is (0.05-0.15):20; and / or The temperature at which the zinc salt reacts with the graphene dispersion is 270° C. to 370° C.; and / or The reaction time of the zinc salt and the graphene dispersion is 25 min to 35 min.
10. The preparation method according to claim 7, characterized in that: The preparation method of the curing agent also includes providing a wetting agent, an anti-settling agent and a second graphene, and mixing the wetting agent, the anti-settling agent and the second graphene with the zinc oxide / graphene composite material, the epoxy curing agent, the naphthalene dispersant and the first solvent to obtain the curing agent.
11. An anti-corrosion coating, characterized in that: The invention comprises an epoxy resin and a curing agent as claimed in any one of claims 1 to 6, or a curing agent prepared by the preparation method as claimed in any one of claims 7 to 10.
12. The anticorrosive coating according to claim 11, characterized in that: The epoxy resin includes one or more of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, aliphatic epoxy resin, and alicyclic epoxy resin; and / or The mass ratio of the epoxy resin to the curing agent is 1:(0.9-1).